Factors predicting survival and pathological subtype in patients with ampullary adenocarcinoma. Issue 2 (12th March 2014) - Okano, Keiichi; Oshima, Minoru; Yachida, Shinichi; Kushida, Yoshio; Kato, Kiyohito; Kamada, Hideki; Wato, Masaki; Nishihira, Tomohiko; Fukuda, Yo; Maeba, Takashi; Inoue, Hideyuki; Masaki, Tsutomu; et al.
<x xml:space="preserve">Abstract</x> Background Carcinoma of the ampulla of Vater is uncommon. This study aimed to clarify predictors of survival for ampullary adenocarcinoma and to identify characteristics of its two major pathological subtypes. Methods Medical records were reviewed for 86 patients who underwent curative resection for ampullary adenocarcinoma between 2000 and 2012 at 12 principal hospitals in Kagawa, Japan. Results Resection was most common among 75–79‐year‐old patients. Actuarial 1‐, 3‐, and 5‐year postoperative survival rates for ampullary adenocarcinoma were 90%, 72.3%, and 69.1%, respectively. Preoperative biliary drainage; serum CA19‐9 and total bilirubin levels; pathological grade; perineural, vascular, pancreatic, and duodenal invasion; nodal metastasis; UICC‐T stage; and pancreatobiliary subtype were predictors of poor survival. An elevated serum CA19‐9 level; an elevated total bilirubin level; lymphatic, vascular, perineural, and pancreatic invasion; and advanced overall tumor stage were more common in patients with pancreatobiliary‐type tumors than in patients with intestinal‐type tumors. Additionally, pathologic subtype analysis showed that each subtype had distinct prognostic factors. Conclusions Preoperative elevated serum CA19‐9 and total bilirubin levels are prognostic factors for ampullary adenocarcinoma, and are both associated with pancreatobiliary‐type tumors. Surgeons should be aware of these factors because pancreatobiliary‐type adenocarcinoma is aggressively invasive and is associated with poor survival. J. Surg. Oncol. 2014; 110:156–162. © 2014 Wiley Periodicals, Inc.